A preliminary study of direct observation and selected water quality monitoring in Putrajaya Lake: the status between October-December 2022 - Azhar, Nur’ain; Yap, Chee Kong; Nulit, Rosimah; Omar, Hishamuddin; Syazwan, Wan Mohd; Leow, Chee Seng (International Journal of Sustainable Energy and Environmental Research, 2024)
The objective of this study was to provide the status of water quality based on a direct observation and selected water quality parameters (nitrite, ammonia, and pH) monitoring study between October-December 2022. Between October and November 2022, the levels of the above three surface water quality parameters were measured in 6 different sites throughout Putrajaya Lake. Observational pictures of the sites were also taken, and water samples were collected. In addition to the above observation and water quality monitoring study, the rainfall data was collected from 17th October 2022 to 11th December 2022, cited from the official website of Public Infobanjir (https://publicinfobanjir.water.gov.my/?lang=en) at stations Sg. Anak Gajah and Sg. Limau Manis, was also used to understand the possible correlation. However, further studies are needed. It was found that the water quality status was in good condition, making Putrajaya Lake a safe and suitable lake for aquatic life and recreational activities between October -December 2022. This could be due to the sustainable practices and rainwater harvesting system already implemented at Putrajaya Lake. Putrajaya Lake’s water quality monitoring and sustainability practices were well implemented. However, regular maintenance to provide acute monitoring of water quality data at Putrajaya Lakes is necessary in the future.